Genetic and Clinical Profiles of Disseminated Bacillus Calmette-Guérin Disease and Chronic Granulomatous Disease in China - Li, Tao; Zhou, Xian; Ling, Yun; Jiang, Ning; Ai, Jingwen; Wu, Jing; Chen, Jiazhen; Chen, Li; Qian, Xiaowen; Liu, Xuhui; Xi, Xiuhong; Xia, Lu; et al. (Frontiers in Immunology, 2019)
Background: Disseminated Bacillus Calmette-Guérin disease (D-BCG) in children with chronic granulomatous disease (CGD) can be fatal, while its clinical characteristics remain unclear because both diseases are extremely rare. The patients with CGD receive BCG vaccination, because BCG vaccination is usually performed within 24 hours after delivery in China. Methods: We prospectively followed-up Chinese patients with CGD who developed D-BCG to characterize their clinical and genetic characteristics. The diagnoses were based on the patients’ clinical, genetic, and microbiological characteristics. Results: Between September 2009 and September 2016, we identified 23 patients with CGD who developed D-BCG. Their overall 10-year survival rate was 34%. We created a simple dissemination score to evaluate the number of infected organ systems and the survival probabilities after 8 years were 62% and 17% among patients with simple dissemination scores of ≤3 and >3, respectively (p = 0.0424). Survival was not significantly associated with the CGD stimulation index or interferon-γ treatment. Eight patients underwent umbilical cord blood transplantation and 5 of them were successfully treated. The genetic analyses found mutations in CYBB (19 patients), CYBA (1 patient), NCF1 (1 patient), and NCF2 (1 patient). We identified 6 novel highly likely pathogenic mutations, including 4 mutations in CYBB and 2 mutations in NCF1. Conclusions: D-BCG is a deadly complication of CGD. The extent of BCG spreading is strongly associated with clinical outcomes, and hematopoietic stem cell transplantation may be a therapeutic option for this condition.